Risk Management in Strategic Sourcing: An African Perspective - Ellsworth Jonathan; Chengedzai Mafini; Joyendu Bhadury (International Journal of Supply Chain Management, 2019)
In this paper we survey existing literature from scholarly journals and practitioner literature published from 1980 to 2017 on the risks and mitigation factors of strategic sourcing in Africa and append the same with a detailed exemplar based on a large utility provider in South Africa.Â The paper identifies the various supply chain risks facing organisations, contextualizing the same for Africa, and where applicable, the mitigation strategies thereof.Â The preliminary finding was that there is generally an underrepresentation of Africa in supply chain management literature. Further, it was found that studies discussing supply chain risk and mitigation issues in Africa have focused mainly on challenges of sourcing in Africa.Â A further observation was that literature provides some limited insights on how supply chain management tools such as total quality management, negotiation and supplier selection, and just-in time procurement may be implemented in African countries. However, the available literature manifests significant limitations in scope, both empirically and theoretically, when compared to the vast amount of contributions from emerging economies in Asia as well as developed economies. The study thus demonstrates that that there exists an untapped opportunity for future research in supply chain risk management in order to develop an integrated framework for risk management in strategic sourcing in Africa.